Plasma fractionation in South Africa: challenges and successes in meeting international standards - Omarjee, Jeh-Han; Germishuizen, Willem Andreas; Chetty, Rangini; Stubbings, David (Annals of Blood; Vol 3 (January 2018): Annals of blood, 2018)
Africa represents a challenge to the provision of plasma-derived medicinal products (PDMPs) as there are many competing health priorities on a continent with limited investment and resources to support some of the poorest nations. To compound this, the availability of suitable plasma, although improving, severely limits better access to PDMP for patients in the region. The National Bioproducts Institute NPC (NBI), as a fractionator in South Africa, illustrates a model of local fractionation which successfully addresses some of the dilemmas faced by lower resourced countries in the broader African context. NBI is a relatively small fractionator in the South African pharmaceutical manufacturing landscape, which is characterised by rigorous local and international regulatory requirements, a volatile currency and restrictive pharmaceutical pricing practices. Further, NBI is confronted by a constantly evolving regulatory and operating environment, a paucity of active raw materials, dynamic market trends and variable patient demand for plasma derivatives, as diagnosis of many of the clinical conditions for which plasma derivatives are indicated, improves. Despite these challenges, NBI remains a sustainable and viable local fractionator, positioned to realise its strategic intent of providing accessible, affordable and a comprehensive range of essential PDMPs to patients in South Africa and the Southern African Development Community region. A key to NBI’s success is the strategic partnerships with the South African Blood Transfusion Services (BTS) and other industry associations, as well as a good working relationship with the local regulatory authority, the South African Health Products Regulatory Authority (SAHPRA).